Orpah and her interpreters : evaluating the justifications for the traditional-stereotyped readings - Michael, Matthew (Old Testament essays, 2011)
The traditional readings of the book of Ruth normally treat Orpah either in the semi-category of a villain or a full-fledged villain who turned her back on Naomi, monotheism, and the messianic lineage and hence disappeared from the sacred history into polytheism. In these traditional Jewish and Christian perspectives, the character Orpah is largely denied presence, importance or voice in the biblical text. This tendency primarily comes from the imposing ideological context of the book of Ruth as a royal story and the subsequent readings of this particular character within this ideological template or even further possible readings in canonical and ecclesiastical mappings. Taking sides with Orpah, this paper evaluates the various interpretative traditions by midrashic, feminist and conservative interpreters. It critiques the justifications for the traditional stereotyped readings and notes the power dynamics involved in Orpah finding herself as a minority in the story of the most powerful royal family in Jewish history.